Thermoplastic resin composition and molded article thereof
By adjusting the ratio of acrylic components and soft elastomers in the thermoplastic resin composition, combining the characteristics of methyl methacrylate units and rubbery polymers, the buffering and feel of the thermoplastic resin composition in the prior art is solved. The disadvantages of this method achieve high grip performance and excellent laser marking effect.
Patent Information
- Application Number
- CN202380044753.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-08
- Filing Date
- 2023-07-26
- Publication Date
- 2025-01-14
AI Technical Summary
The existing thermoplastic resin compositions for laser marking cannot fully meet the needs of multi-handheld use or operating equipment in terms of buffering, hand feeling and touch, especially for multi-touch contact products such as OA devices, home appliances and automotive interior components.
The thermoplastic resin composition containing a reinforcement resin containing acrylic acid component and a soft elastomer is met by a specific ratio, and the ratio requirements of 0.1 < Y/(X+Y) < 0.9 are optimized, and the softness and laser marking are combined with methyl groups. The content of methyl acrylate units and the volume average particle size of rubbery polymers improve the grip performance and optical characteristics of the molded product.
It realizes excellent laser marking, softness, non-sliding and high grip performance, and takes into account good optical characteristics and is suitable for equipment and components for multi-handheld use or operation.
Smart Images

Figure BDA0005167395160000222 
Figure BDA0005167395160000231
Abstract
Description
Technical Field
[0001] The present invention relates to a thermoplastic resin composition which can obtain excellent laser marking properties (color development of the irradiated part) and is soft, thereby being able to realize a molded product having good touch, non-slip, high grip performance, and excellent optical properties. In addition, the present invention also relates to a molded product obtained by molding the thermoplastic resin composition and an article obtained by laser marking the molded product. Background Art
[0002] As methods for marking characters, symbols, pictures, etc. on the surface of a resin molded product, pad printing using ink, screen printing, and laser marking using laser irradiation are known. Laser marking includes, for example, the following methods (1) and (2).
[0003] (1) A method of irradiating a resin molded product that uses a black substance to present a dark color by laser, and using the energy of the laser to show chemical changes of the resin in the irradiated part, chemical changes of the black substance, etc., so that the irradiated part is colored in the color of the resin (white), etc., to form text, symbols, pictures, etc. (see Patent Documents 1 and 2).
[0004] (2) A method of placing a marking composition on the surface of an article and irradiating the article with laser light to perform marking (see Patent Document 3).
[0005] Among them, in the method of patent document 3, since the marking composition is arranged on the surface of the article and laser irradiation is performed, the number of processing steps such as molding of the molded product, arrangement of the marking composition, and laser irradiation is large, and the productivity is poor. In addition, it is not suitable for large and complex-shaped articles such as vehicles.
[0006] The thermoplastic resin composition for laser marking of Patent Document 1 can provide a molded product having excellent physical properties such as impact resistance and heat resistance and coloring appearance, and can clearly show characters, marks, pictures, etc. by irradiating the surface with laser light through the color development of the irradiated part. However, there is room for improvement in the cushioning properties, hand feel, and tactile feel of the obtained molded product.
[0007] Patent Document 2 discloses a butadiene rubber reinforced resin composition for laser marking, which can be used to develop a white color by laser marking a transparent ABS resin. However, similar to Patent Document 1, the cushioning properties, hand feel, and tactile feel of the resulting molded product still need to be improved.
[0008] Examples of molded products for laser marking include molded products in a wide range of fields, such as OA equipment, home appliances, automobile parts, sundries, and building materials. Among them, for OA equipment such as personal computers and printers that are often used or operated by hand; home appliances such as cameras, camcorders, vacuum cleaners, and washing machines; and automobile interior parts such as door trims and glove boxes that are frequently touched by the body of the passenger, it is required to maintain the rigidity of the parts while maintaining good cushioning properties, feel, and other tactile properties.
[0009] However, conventional thermoplastic resin compositions for laser marking cannot fully satisfy the required properties in terms of cushioning, texture, and tactile feel.
[0010] Prior art literature
[0011] Patent Literature
[0012] Patent Document 1: Japanese Patent Application Publication No. 2012-102271
[0013] Patent Document 2: Japanese Patent Application Publication No. 2002-003548
[0014] Patent Document 3: International Publication No. 2007 / 072694 Summary of the invention
[0015] Problems to be solved by the invention
[0016] The present invention aims to provide a thermoplastic resin composition which has excellent laser marking properties (color development of the irradiated portion) and is soft, thereby enabling the realization of a molded product having a good touch, being non-slip, having high gripping properties, and having excellent optical properties; and to provide a molded product obtained by molding the thermoplastic resin composition and an article obtained by laser marking the molded product.
[0017] Means for solving problems
[0018] The present inventors have found that the above-mentioned object can be achieved by using a thermoplastic resin composition comprising a reinforcing resin (A) containing an acrylic component and a soft elastomer (B) in a specific ratio.
[0019] That is, the gist of the present invention is as follows.
[0020] [1] A thermoplastic resin composition comprising the following components (A) and (B), wherein when the content of methyl methacrylate units in the total of 100% by mass of the components (A) and (B) is X% by mass and the content of the component (B) is Y% by mass, the composition satisfies the following formula (1).
[0021] 0.1 <Y / (X+Y)<0.9…(1)
[0022] Component (A): a reinforcing resin containing an acrylic component, which is composed of a rubber-containing graft copolymer (a1) having a durometer hardness (type A) of 90 or more, or the rubber-containing graft copolymer (a1) and a (co)polymer (a2) not containing a rubber polymer, wherein the rubber-containing graft copolymer (a1) and / or the (co)polymer (a2) contain methyl methacrylate units;
[0023] Component (B): A soft elastomer having a durometer hardness (type A) of less than 90.
[0024] [2] The thermoplastic resin composition according to [1], wherein the content Y of the component (B) in 100% by mass of the total of the component (A) and the component (B) exceeds 20.0% by mass.
[0025] [3] The thermoplastic resin composition described in [1] or [2], wherein the rubber-containing graft copolymer (a1) is one or more selected from the group consisting of methyl methacrylate-acrylonitrile-butadiene-styrene graft copolymer, acrylonitrile-styrene-acrylic rubber graft copolymer, methyl methacrylate-acrylonitrile-styrene-acrylic rubber graft copolymer and acrylonitrile-butadiene-styrene graft copolymer.
[0026] [4] The thermoplastic resin composition according to any one of [1] to [3], which is a thermoplastic resin composition for laser marking.
[0027] [5] A molded article obtained by molding the thermoplastic resin composition according to any one of [1] to [4].
[0028] [6] An article obtained by laser marking the surface of the molded article described in [5].
[0029] Effects of the Invention
[0030] According to the present invention, it is possible to provide a thermoplastic resin composition which has excellent laser marking properties (color rendering of the irradiated portion) and is soft, thereby being able to realize a molded product which has a good touch, is not easy to slide, has high grip performance, and has excellent optical properties; and to provide a molded product obtained by molding the thermoplastic resin composition and an article obtained by laser marking the molded product. DETAILED DESCRIPTION
[0031] The embodiments of the present invention are described in detail below.
[0032] In this specification, "(co)polymer" means a homopolymer and / or a copolymer.
[0033] The "molded article" refers to an article obtained by molding a thermoplastic resin composition.
[0034] "Unit" refers to a structural part that is derived from a monomer compound (monomer) before polymerization and is introduced into a polymer or copolymer. For example, "methyl methacrylate unit" refers to "a structural part that is derived from methyl methacrylate and is introduced into a polymer or copolymer." "Aromatic vinyl monomer unit" refers to "a structural part that is derived from an aromatic vinyl monomer and is introduced into a polymer or copolymer."
[0035] “(Meth)acrylic acid” means one or both of “acrylic acid” and “methacrylic acid”.
[0036] [Thermoplastic resin composition]
[0037] The thermoplastic resin composition of the present invention is characterized in that it contains the following components (A) and (B), and when the content of methyl methacrylate units in the total of 100% by mass of the components (A) and (B) is X% by mass and the content of the component (B) is Y% by mass, the following formula (1) is satisfied. The thermoplastic resin composition of the present invention is particularly suitable as a thermoplastic resin composition for laser marking.
[0038] 0.1 <Y / (X+Y)<0.9…(1)
[0039] Component (A): a reinforced resin containing an acrylic component (hereinafter sometimes referred to as "reinforced resin containing an acrylic component (A)"), which is composed of a rubber-containing graft copolymer (a1) having a durometer hardness (type A) of 90 or more, or the rubber-containing graft copolymer (a1) and a (co)polymer (a2) not containing a rubbery polymer, wherein the rubber-containing graft copolymer (a1) and / or the (co)polymer (a2) contain methyl methacrylate units;
[0040] Component (B): a soft elastomer having a durometer hardness (type A) of less than 90 (hereinafter sometimes referred to as "soft elastomer (B)").
[0041] [Formula (1)]
[0042] The thermoplastic resin composition of the present invention satisfies the following formula (1) when the content of methyl methacrylate units in 100% by mass of the total of the components (A) and (B) is X% by mass and the content of the component (B) is Y% by mass.
[0043] 0.1 <Y / (X+Y)<0.9…(1)
[0044] When Y / (X+Y) is less than 0.1, the flexibility is poor, and when it is greater than 0.9, the laser marking property is poor. When Y / (X+Y) exceeds 0.1 and is less than 0.9, that is, when the above formula (1) is satisfied, both the flexibility and the laser marking property become good.
[0045] From the viewpoint of achieving both flexibility and laser marking properties, the thermoplastic resin composition of the present invention preferably satisfies the following formula (1A), and more preferably satisfies the following formula (1B).
[0046] 0.2≤Y / (X+Y)≤0.8…(1A)
[0047] 0.3≤Y / (X+Y)≤0.7…(1B)
[0048] [Acrylic-containing reinforcing resin (A)]
[0049] The acrylic reinforcing resin (A) is composed of a rubber-containing graft copolymer (a1) having a durometer hardness (type A) of 90 or more, or the rubber-containing graft copolymer (a1) and a (co)polymer (a2) that does not contain a rubbery polymer. The rubber-containing graft copolymer (a1) and / or the (co)polymer (a2) contain methyl methacrylate units. That is, the content of methyl methacrylate units in 100% by mass of the acrylic reinforcing resin (A) is greater than 0% by mass.
[0050] <Rubber-Containing Graft Copolymer (a1)>
[0051] Examples of the rubber-containing graft copolymer (a1) include methyl methacrylate-acrylonitrile-butadiene-styrene graft copolymer (MABS resin), acrylonitrile-styrene-acrylic rubber graft copolymer (ASA resin), methyl methacrylate-acrylonitrile-styrene-acrylic rubber graft copolymer (MASA resin), acrylonitrile-butadiene-styrene graft copolymer (ABS resin), methyl methacrylate-acrylic rubber-styrene graft copolymer (MSA resin), and the like.
[0052] Among them, as the rubber-containing graft copolymer (a1), from the perspective of laser marking properties, preferred are methyl methacrylate-acrylonitrile-butadiene-styrene graft copolymer (MABS resin), acrylonitrile-styrene-acrylic rubber graft copolymer (ASA resin), methyl methacrylate-acrylonitrile-styrene-acrylic rubber graft copolymer (MASA resin), and acrylonitrile-butadiene-styrene graft copolymer (ABS resin), and more preferred are methyl methacrylate-acrylonitrile-styrene-butadiene graft copolymer (MABS resin) and methyl methacrylate-acrylonitrile-acrylic rubber-styrene graft copolymer (MASA resin).
[0053] The acrylic component-containing reinforcing resin (A) may contain only one type of these rubber-containing graft copolymers (a1), or may contain two or more types of these rubber-containing graft copolymers (a1).
[0054] The rubber-containing graft copolymer (a1) of the present invention can be preferably produced by graft-copolymerizing the following vinyl monomer mixture (a1-2) in the presence of the following rubbery polymer (a1-1).
[0055] (Rubbery polymer (a1-1))
[0056] The rubbery polymer (a1-1) of the rubber-containing graft copolymer (a1) used to constitute the reinforcing resin (A) containing acrylic components is not particularly limited, and examples thereof include diene rubber, acrylic rubber, ethylene rubber, and the like. Specifically, polybutadiene, poly(butadiene-styrene), poly(butadiene-acrylonitrile), polyisoprene, poly(butadiene-butyl acrylate), poly(butadiene-methyl acrylate), poly(butadiene-methyl methacrylate), poly(butadiene-ethyl acrylate), ethylene-propylene rubber, ethylene-propylene-diene rubber, poly(ethylene-isobutylene), poly(ethylene-methyl acrylate), poly(ethylene-ethyl acrylate), and the like can be cited. One or a mixture of two or more of these rubbery polymers can be used. Among them, diene rubber and acrylic rubber are particularly preferably used from the aspect of laser marking properties.
[0057] The volume average particle size of the rubber polymer (a1-1) is preferably 90 to 1500 nm, more preferably 150 to 1000 nm, and even more preferably 200 to 500 nm, from the viewpoint of impact resistance, moldability, fluidity and appearance of the obtained thermoplastic resin composition.
[0058] Here, the volume average particle size of the rubber polymer (a1-1) is measured by the method described in the section of Examples described later.
[0059] (Vinyl Monomer Mixture (a1-2))
[0060] The vinyl monomer mixture (a1-2) is preferably a vinyl monomer mixture containing at least an aromatic vinyl monomer and a cyanide vinyl monomer, or a vinyl monomer mixture containing at least an alkyl (meth)acrylate monomer.
[0061] As the aromatic vinyl monomer, styrene, α-methylstyrene, p-methylstyrene, vinyltoluene, tert-butylstyrene, o-ethylstyrene, o-chlorostyrene, o-, p-dichlorostyrene can be mentioned. These monomers can be used alone or in combination of two or more.
[0062] Examples of the vinyl cyanide monomer include acrylonitrile, methacrylonitrile, and ethacrylonitrile. Of these, acrylonitrile is particularly preferred. The vinyl cyanide monomer may be used alone or in combination of two or more.
[0063] In the case of a vinyl monomer mixture containing at least an aromatic vinyl monomer and a cyanide vinyl monomer, from the aspects of moldability and appearance of the molded article, the ratio of the aromatic vinyl monomer to the cyanide vinyl monomer in 100% by mass of the vinyl monomer mixture (a1-2) is preferably aromatic vinyl monomer / cyanide vinyl monomer = 50 to 95% by mass / 50 to 5% by mass, more preferably 60 to 85% by mass / 40 to 15% by mass, and further preferably 65 to 80% by mass / 35 to 20% by mass.
[0064] In the vinyl monomer mixture (a1-2) as a vinyl monomer mixture containing at least an aromatic vinyl monomer and a cyanide vinyl monomer, in addition to the aromatic vinyl monomer and the cyanide vinyl monomer, other vinyl monomers that can copolymerize with them can be contained in the range of 0 to 30% by mass. As other vinyl monomers that can copolymerize with them, unsaturated carboxylic acid ester monomers such as methyl (meth)acrylate; maleimide monomers such as N-methylmaleimide, N-cyclohexylmaleimide, and N-phenylmaleimide; unsaturated dicarboxylic acids such as maleic acid; unsaturated dicarboxylic anhydrides such as maleic anhydride; unsaturated amides such as acrylamide; etc., one or more of the above, but not limited to these. Among them, methyl (meth)acrylate, N-phenylmaleimide, and maleic anhydride are preferred.
[0065] As the (meth)acrylic acid alkyl ester monomer, there can be mentioned an (meth)acrylic acid alkyl ester monomer in which the carbon number of the alkyl group is 1 to 8. As the (meth)acrylic acid alkyl ester monomer, there can be mentioned, for example, methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, pentyl (meth)acrylate, n-hexyl (meth)acrylate, n-octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, cyclohexyl (meth)acrylate, etc. Among these, methyl methacrylate is preferred from the aspect of color development based on laser marking.
[0066] In the vinyl monomer mixture (a1-2) as a vinyl monomer mixture containing at least (meth) alkyl acrylate monomers, in addition to the (meth) alkyl acrylate monomers, other vinyl monomers copolymerizable with them may be contained in the range of 0 to 30% by mass. As other vinyl monomers copolymerizable with them, there can be cited the vinyl monomers used in the vinyl monomer mixture (a1-2) as a vinyl monomer mixture containing at least an aromatic vinyl monomer and a cyanide vinyl monomer, and the vinyl monomers other than the (meth) acrylate monomers described above.
[0067] (Ratio of rubber polymer (a1-1) to vinyl monomer mixture (a1-2))
[0068] The graft copolymer (a1) is preferably obtained by graft polymerization of 20 to 65% by weight of a vinyl monomer mixture (a1-2) in the presence of 35 to 80% by weight of a rubber polymer (a1-1), wherein the total amount of the rubber polymer (a1-1) and the vinyl monomer mixture (a1-2) is 100% by weight.
[0069] If the rubber polymer (a1-1) is less than 35% by mass and the vinyl monomer mixture (a1-2) exceeds 65% by mass, the resulting thermoplastic resin composition has poor softness. When the rubber polymer (a1-1) exceeds 80% by mass and the vinyl monomer mixture (a1-2) is less than 20% by mass, the optical properties of the resulting thermoplastic resin composition are reduced. The proportion of the rubber polymer (a1-1) is more preferably 45 to 78% by mass, and more preferably 53 to 73% by mass, and the proportion of the vinyl monomer mixture (a1-2) is more preferably 22 to 55% by mass, and more preferably 27 to 47% by mass.
[0070] (Graft Polymerization)
[0071] The method for producing the rubber-containing graft copolymer (a1) by graft polymerization is not particularly limited, and the rubber-containing graft copolymer (a1) can be produced by any method such as a known emulsion polymerization method, a suspension polymerization method, a continuous bulk polymerization method, a continuous solution polymerization method, etc. The rubber-containing graft copolymer (a1) is preferably produced by an emulsion polymerization method or a bulk polymerization method. From the perspective of easily adjusting the emulsifier content and the water content in the rubber-containing graft copolymer (a1), the rubber-containing graft copolymer (a1) is most preferably produced by an emulsion polymerization method.
[0072] (Grafting rate)
[0073] In the rubber-containing graft copolymer (a1), the total amount of the vinyl monomer mixture (a1-2) is not necessarily grafted, and a mixture with an ungrafted copolymer is usually used. This mixture is originally a composition, but is included in the graft copolymer (a1) in the present invention.
[0074] The graft ratio of the rubber-containing graft copolymer (a1) is not limited, but is preferably 20 to 100% by mass, more preferably 30 to 80% by mass, and even more preferably 40 to 70% by mass from the viewpoint of the impact resistance of the obtained thermoplastic resin composition.
[0075] The graft ratio of the rubber-containing graft copolymer (a1) is measured by the method described in the section of Examples described later.
[0076] (Durometer hardness (Type A))
[0077] It is a necessary condition that the durometer hardness (type A) of the rubber-containing graft copolymer (a1) used in the present invention is 90 or more. When the durometer hardness (type A) of the rubber-containing graft copolymer (a1) is less than 90, it is not preferred from the perspective of molding processability and fluidity. From the perspective of softness, molding processability and fluidity, the durometer hardness (type A) of the rubber-containing graft copolymer (a1) is preferably 90 or more.
[0078] The durometer hardness (type A) of the rubber-containing graft copolymer (a1) is measured by the method described in the section of Examples described later.
[0079] <(Co)polymer (a2)>
[0080] As the (co)polymer (a2) not containing a rubber polymer used for the reinforcing resin (A) containing an acrylic component, for example, styrene resins such as acrylonitrile-styrene copolymer (AS) and methyl acrylate-acrylonitrile-styrene copolymer (MAS), polyacrylic resins, etc. These (co)polymers (a2) may be used alone or in combination of two or more.
[0081] (Styrene resin)
[0082] The mass average molecular weight (Mw) of the styrene resin is preferably 50,000 to 400,000, more preferably 70,000 to 350,000, and even more preferably 90,000 to 300,000. The molecular weight distribution (Mw / Mn) is preferably 1.3 to 2.8, more preferably 1.8 to 2.6, and even more preferably 1.9 to 2.4.
[0083] Here, the mass average molecular weight and molecular weight distribution of the styrene-based resin can be measured as polystyrene-equivalent values based on GPC (gel permeation chromatography).
[0084] The styrene-based resin may be used alone or in combination of two or more styrene-based resins having different monomer compositions, molecular weights, etc.
[0085] From the perspective of moldability and appearance of molded products, in the styrene resin, the ratio of the aromatic vinyl monomer unit to the cyanide vinyl monomer unit in 100% by mass of the acrylonitrile-styrene resin is preferably aromatic vinyl monomer unit / cyanide vinyl monomer unit = 50 to 95% by mass / 50 to 5% by mass, more preferably 60 to 85% by mass / 40 to 15% by mass, and further preferably 65 to 80% by mass / 35 to 20% by mass.
[0086] When the total content of the three structural units of the methyl acrylate-acrylonitrile-styrene copolymer is 100 mass%, the content of the structural unit derived from the aromatic vinyl compound is preferably 5 to 50 mass%, more preferably 15 to 25 mass%, the content of the structural unit derived from the vinyl cyanide compound is preferably 4 to 25 mass%, more preferably 5 to 15 mass%, and the content of the structural unit derived from methyl acrylate is preferably 55 to 80 mass%, more preferably 60 to 75 mass%.
[0087] <Polyacrylic acid resin>
[0088] The polyacrylic resin is obtained by polymerizing a vinyl monomer or a vinyl monomer mixture containing a (meth)acrylate monomer using a known method. The vinyl monomer mixture contains a (meth)acrylate monomer as an essential component and may contain other vinyl monomers as shown below in a range of 40% by mass or less as required.
[0089] Examples of the (meth)acrylate monomer include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, and phenyl (meth)acrylate.
[0090] As other vinyl monomers other than (meth)acrylate monomers, for example, aromatic vinyl monomers, cyanide vinyl monomers, maleimide monomers, (meth)acrylic acid, etc. Aromatic vinyl monomers and cyanide vinyl monomers can be the same as those contained in the above-mentioned vinyl monomer mixture (a1-2).
[0091] Examples of maleimide monomers include N-alkylmaleimides (N-methylmaleimide, N-ethylmaleimide, N-n-propylmaleimide, N-isopropylmaleimide, N-n-butylmaleimide, N-isobutylmaleimide, N-tert-butylmaleimide, etc.), N-cycloalkylmaleimide (N-cyclohexylmaleimide, etc.), and N-arylmaleimide (N-phenylmaleimide, N-alkyl-substituted phenylmaleimide, N-chlorophenylmaleimide, etc.).
[0092] Among the polyacrylic acid resins, specific examples of copolymer resins of methyl methacrylate and methyl acrylate include commercially available products such as "Parapet (registered trademark) G" manufactured by KURARAY, "ACRYPET (registered trademark) VH" and "ACRYPET (registered trademark) MD" manufactured by Mitsubishi Chemical Corporation. In addition, specific examples of polyacrylic acid resins containing both (meth)acrylate monomer units and maleimide monomer units include commercially available products such as "Parapet (registered trademark) SH-N" manufactured by KURARAY, and "Polyimilex (registered trademark) PML203" manufactured by Nippon Shokubai Co., Ltd.
[0093] These polyacrylic acid-based resins may be used alone or in combination of two or more.
[0094] <Ratio of the rubber-containing graft copolymer (a1) to the (co)polymer (a2)>
[0095] The acrylic reinforcing resin (A) may be composed of the above-mentioned rubber-containing graft copolymer (a1) alone, or may be composed of the rubber-containing graft copolymer (a1) and the (co)polymer (a2). In either case, the rubber-containing graft copolymer (a1) or the rubber-containing graft copolymer (a1) and the (co)polymer (a2) are used as the acrylic reinforcing resin (A) in a manner that satisfies the above-mentioned formula (1), and more preferably satisfies the preferred methyl methacrylate unit content of the acrylic reinforcing resin (A) described below, and the preferred rubber polymer (a1-1) content of the thermoplastic resin composition of the present invention described later.
[0096] <Methyl methacrylate unit content>
[0097] The acrylic component-containing reinforcing resin (A) contains methyl methacrylate units by causing the rubber-containing graft copolymer (a1) and / or (co)polymer (a2) constituting the acrylic component-containing reinforcing resin (A) to contain methyl methacrylate units.
[0098] The content of the methyl methacrylate unit of the acrylic component-containing reinforcing resin (A) is not particularly limited as long as it satisfies the above formula (1). However, from the viewpoint of easily satisfying the above formula (1) while ensuring an appropriate content of the soft elastomer (B) in the thermoplastic resin composition, the content is preferably 8.0 to 75.0% by mass, particularly preferably 8.5 to 73.5% by mass.
[0099] [Soft elastomer (B)]
[0100] The soft elastomer (B) contained in the thermoplastic resin composition of the present invention has a durometer hardness (type A) of less than 90. The soft elastomer (B) is not particularly limited as long as it is a polymer that can be molded by heating and melting to provide a molded product having rubber elasticity. The soft elastomer (B) can be molded by heating and melting, but the graft copolymer containing diene rubber and the graft copolymer containing non-diene rubber used as the rubber-containing graft copolymer (a1) are different in that they cannot be molded by heating and melting.
[0101] The durometer hardness (type A) of the soft elastomer (B) is less than 90. If the durometer hardness (type A) of the soft elastomer (B) is 90 or more, softness cannot be obtained. However, if the durometer hardness (type A) of the soft elastomer (B) is too small, it is not preferred from the aspects of molding processability and fluidity. The durometer hardness (type A) of the soft elastomer (B) is preferably 20 or more and less than 90, more preferably 40 to 80.
[0102] Specific examples of the soft elastomer (B) include acrylic elastomers, styrene elastomers, diene elastomers such as polybutadiene elastomers, olefin elastomers, polyurethane elastomers, polyvinyl chloride elastomers, ester elastomers, fluororesin elastomers, and ionomers.
[0103] Specific examples of the acrylic elastomer include soft acrylic resins.
[0104] Commercially available soft acrylic resins may be used, and specific examples thereof include Trizect series (trade name, manufactured by Aronkasei Co., Ltd.), Kurarity (registered trademark) series (trade name, manufactured by Kuraray Co., Ltd.), and Parapet (registered trademark) series (trade name, manufactured by Kuraray Co., Ltd.).
[0105] As specific examples of styrene-based elastomers, block copolymers containing polymer blocks P of one or more aromatic vinyl compounds and polymer blocks Q of conjugated diene compounds, and hydrogenated products thereof, can be cited. Polymer blocks P and polymer blocks Q may be bonded in a linear or radial manner. In addition, polymer block Q may be a random copolymer containing a small amount of aromatic vinyl compounds as structural units, or a so-called tapered block in which the content of structural units derived from aromatic vinyl compounds gradually increases.
[0106] There is no particular limitation on the structure of the block copolymer, and any of (PQ)n type, (PQ)nP type or (PQ)nC type can be used. Here, P represents a polymer block of an aromatic vinyl compound, Q represents a polymer block of a conjugated diene compound, C represents a coupling agent residue, and n represents an integer greater than 1.
[0107] As the aromatic vinyl compound constituting the structural unit of the polymer block P of the styrene-based elastomer, all of the aromatic vinyl compounds exemplified as the aromatic vinyl monomers contained in the above-mentioned vinyl monomer mixture (a1-2) can be used, and styrene is preferably used. These aromatic vinyl compounds can be used alone or in combination of two or more.
[0108] As the conjugated diene compound constituting the structural unit of the polymer block Q of the styrene-based elastomer, 1,3-butadiene, isoprene, 2-methyl-1,3-butadiene, 2,3-diethyl-1,3-butadiene, 2-neopentyl-1,3-butadiene, 2-chloro-1,3-butadiene, 2-cyano-1,3-butadiene, substituted straight-chain conjugated pentadienes, straight-chain and side-chain conjugated hexadiene, etc. can be mentioned. Among these, 1,3-butadiene, isoprene and 2-methyl-1,3-butadiene are preferred. These conjugated diene compounds can be used alone or in combination of two or more.
[0109] The content of the polymer block P of the styrene elastomer is preferably 5 to 60% by mass, more preferably 15 to 50% by mass. The content of the polymer block Q is preferably 95 to 40% by mass, more preferably 85 to 50% by mass. If the content of the polymer blocks P and Q is within the above range, the touch (grip) and non-slip properties of the molded article using the obtained thermoplastic resin composition become good.
[0110] The styrene elastomer composed of the above-mentioned block copolymer of non-hydrogenated product can be manufactured by block copolymerization according to a conventional method. The hydrogenated product of the block copolymer can be obtained by hydrogenating the polymer block Q of the conjugated diene compound of the block copolymer thus obtained using a known method. As a specific method, there are Japanese Patent Publication No. 42-8704, Japanese Patent Publication No. 43-6636, Japanese Patent Publication No. 63-4841, Japanese Patent Publication No. 63-5401, Japanese Patent Publication No. 2-133406, and Japanese Patent Publication No. 1-297413.
[0111] In the hydrogenation reaction, in the case of a conjugated diene polymer in which the polymer block Q is a polymer block of 1,3-butadiene, when non-selective hydrogenation is performed, ethylene is generated from the portion polymerized with a 1,4-vinyl bond, butene is generated from the portion polymerized with a 1,2-vinyl bond, and styrene-ethylene-butylene-styrene copolymer (SEBS) and the like are generated as hydrogenates. On the other hand, when the 1,2-vinyl bond is selectively hydrogenated, styrene-butadiene-butylene-styrene copolymer (SBBS) and the like are generated as hydrogenates.
[0112] Preferred specific examples of the above-mentioned styrene-based elastomers include styrene-butadiene-styrene block copolymers (SBS), styrene-ethylene-butylene-styrene copolymers (SEBS), styrene-butadiene-butylene-styrene copolymers (SBBS), styrene-isoprene-styrene copolymers (SIS), etc. Among them, styrene-ethylene-butylene-styrene copolymers (SEBS) are particularly suitable from the aspects of tactile feel (grip feeling) and non-slip properties.
[0113] Styrene-ethylene-butylene-styrene copolymer (SEBS) can use commercially available products. As specific examples of commercially available products, Dynaron (registered trademark) series (trade name, JSR Corporation), Lavalon (registered trademark) series (trade name, Mitsubishi Chemical Corporation), Tuftec (registered trademark) series (trade name, Asahi Kasei Corporation), TPE-SB series (trade name, Sumitomo Chemical Industries, Ltd.), etc. can be cited.
[0114] As soft elastomers (B) other than acrylic elastomers and styrene elastomers, for example, high cis-butadiene rubber (BR) and low cis-butadiene rubber (BR), high cis-isoprene rubber (IR), emulsion polymerization and solution polymerization styrene-butadiene rubber (SBR), acrylonitrile-butadiene rubber (NBR), ethylene-propylene rubber (EPM, EPDM), chloroprene rubber, butyl rubber, natural rubber (NR), etc. can be mentioned.
[0115] The soft elastomer (B) such as acrylic elastomer and styrene elastomer may be used alone or in combination of two or more soft elastomers (B) different in type, structure, constituent unit, physical properties, etc.
[0116] [Content ratio of component (A) and component (B)]
[0117] The thermoplastic resin composition of the present invention preferably contains less than 95.0% by mass, preferably 50% by mass or more and less than 80.0% by mass, more preferably 55.0 to 79.9% by mass of the component (A), and contains more than 5% by mass, preferably more than 20% by mass and less than 50% by mass, more preferably 21.1 to 45.0% by mass of the component (B), out of 100% by mass of the total of the components (A) and (B). That is, it is preferred that Y in the above formula (1) exceeds 5% by mass, preferably exceeds 20% by mass and less than 50% by mass, more preferably 21.1 to 45.0% by mass.
[0118] When the content ratio of component (A) to component (B) is within the above range, laser markability and softness can be highly balanced. Regarding softness, the average friction MIU value (grip), durometer hardness type D, and bending elastic modulus (softness) are all good.
[0119] [Rubber polymer (a1-1) content]
[0120] The thermoplastic resin composition of the present invention preferably contains 2 to 35% by mass, particularly 5 to 35% by mass, and especially 8 to 33% by mass of a rubber polymer (a1-1) derived from a rubber-containing graft copolymer (a1) in 100% by mass of the thermoplastic resin composition. If the content of the rubber polymer (a1-1) in the thermoplastic resin composition is above the above lower limit, the touch (gripability), non-slip properties, and softness become good, and if it is below the above upper limit, the optical properties become good.
[0121] [Methyl methacrylate unit content]
[0122] The thermoplastic resin composition of the present invention preferably contains more than 2.0 mass%, preferably 5.0 to 70.0 mass%, and more preferably 13.5 to 70.0 mass% of methyl methacrylate units derived from component (A) in 100 mass% of the total of component (A) and component (B). That is, preferably, X in the above formula (1) is more than 2.0 mass%, preferably 5.0 to 70.0 mass%, and more preferably 13.5 to 70.0 mass%. If the content of methyl methacrylate units in the thermoplastic resin composition is within the above range, the color development (clarity and visibility) of the irradiated portion in the laser marking becomes good.
[0123] [Inorganic compounds (D)]
[0124] The thermoplastic resin composition of the present invention has improved moldability by containing the inorganic compound (D). In addition, the morphology of the obtained molded article can be stabilized by containing the inorganic compound (D).
[0125] Examples of the inorganic compound (D) include metal fibers, aramid fibers, asbestos, potassium titanate whiskers, wollastonite, glass flakes, glass beads, talc, mica, clay, calcium carbonate, barium sulfate, titanium oxide, and aluminum oxide.
[0126] The inorganic compound (D) is preferably in a flat plate, a linear shape, or a scaly shape, and more preferably in a plate or a scaly shape from the viewpoint of the appearance of the resulting molded article.
[0127] As the inorganic compound (D), the volume average particle size determined by laser diffraction is preferably 1 to 200 μm. The volume average particle size is more preferably 2 to 120 μm, further preferably 10 to 80 μm, and particularly preferably 15 to 40 μm. If the volume average particle size of the inorganic compound (D) is above the lower limit, the balance between moldability and softness becomes good, and if it is below the upper limit, the optical properties become good.
[0128] The ratio of the volume average particle size to the thickness (aspect ratio) of the inorganic compound (D) is preferably 5 to 150, more preferably 10 to 120, and even more preferably 40 to 90. When the aspect ratio is greater than or equal to the above lower limit, the balance between moldability and softness becomes good, and when it is less than or equal to the above upper limit, the touch (gripability) and non-slip properties become good.
[0129] The inorganic compound (D) may be used alone or in combination of two or more kinds of compounds having different materials, shapes, etc.
[0130] Among them, the inorganic compound (D) is preferably titanium oxide, talc, mica, and calcium carbonate, and mica is particularly preferred from the viewpoint of appearance.
[0131] Mica includes dry-crushed mica and wet-crushed mica, and wet-crushed mica is preferred, and wet-crushed muscovite is particularly preferred. This is because wet-crushed silica has a higher purity than dry-crushed silica and does not affect the appearance, so it has a high utilization value.
[0132] When the thermoplastic resin composition of the present invention contains an inorganic compound (D), the content of the inorganic compound (D) is preferably 0 to 10% by mass, more preferably 0.5 to 5.5% by mass, and further preferably 3 to 15% by mass relative to 100% by mass of the total of component (A) and component (B). If the content of the inorganic compound (D) is above the lower limit, the above-mentioned effect brought about by the use of the inorganic compound (D) can be fully obtained, and if it is below the upper limit, the mechanical properties, the appearance of the molded product, etc. will not be impaired.
[0133] [Other additives]
[0134] The thermoplastic resin composition of the present invention may contain various additives in order to improve the performance as a molding resin within the range not impairing the object of the present invention.
[0135] For example, antioxidants such as hindered phenols, sulfur-containing organic compounds, and phosphorus-containing organic compounds can be added as needed; various stabilizers such as phenols, acrylates, and other heat stabilizers, ester exchange inhibitors such as a mixture of monostearyl acid phosphate and distearyl acid phosphate, benzotriazoles, benzophenones, salicylates, and other ultraviolet absorbers, organic nickel, hindered amines, and other light stabilizers can be added; lubricants such as metal salts of higher fatty acids and higher fatty amides can be added; plasticizers such as phthalates and phosphates can be added; halogen-containing compounds such as polybrominated diphenyl ethers, tetrabromobisphenol-A, brominated epoxy oligomers, brominated polycarbonate oligomers, phosphorus compounds, antimony trioxide, and other flame retardants / flame retardant additives can be added; carbon black, pigments, and dyes can be added.
[0136] Among them, by mixing about 0.001 to 5 parts by mass of carbon black having a particle size of about 10 to 80 nm with respect to 100 parts by mass of the components (A) and (B), excellent color development and visibility by laser marking are achieved.
[0137] [Method for producing thermoplastic resin composition]
[0138] The thermoplastic resin composition of the present invention can be produced by various methods such as melt-kneading the above-mentioned components (A) and (B), the inorganic compound (D) used as required, and the above-mentioned additives using a Banbury mixer, a roll, a single-screw extruder, or a multi-screw extruder.
[0139] [Molding products]
[0140] The molded article of the present invention is obtained by molding the thermoplastic resin composition of the present invention by a known molding method, such as injection molding, compression molding, extrusion molding, vacuum molding, blow molding, and the like.
[0141] The molded article of the present invention obtained by molding the thermoplastic resin composition of the present invention has excellent laser marking properties (color development of the irradiated portion), is not easy to slide, and has high gripping performance. Therefore, the molded article of the present invention is used not only as a gripping surface but also as a part of a housing in electrical / electronic parts, automobile parts, mechanical parts, OA equipment, or housing parts of home appliances, general sundries, residential building materials, etc., and can be laser marked on its surface.
[0142] [thing]
[0143] The article of the present invention is obtained by subjecting the molded article of the present invention, which is obtained by molding the thermoplastic resin composition of the present invention, to laser marking.
[0144] As the laser used for laser marking, gas lasers such as He-Ne laser, Ar laser, CO2 laser, and excimer laser, solid lasers such as YAG laser, semiconductor laser, and dye laser can be used. In the present invention, CO2 laser, excimer laser, YAG laser, etc. are preferably used.
[0145] Example
[0146] The present invention will be described in more detail below with reference to Examples and Comparative Examples. The present invention is not limited to the following Examples unless it exceeds the gist of the present invention.
[0147] Unless otherwise specified, "%" means % by mass, and "part(s)" means parts by mass.
[0148] [Measurement method]
[0149] The volume average particle size of the rubber polymer (a1-1), the grafting rate of the rubber-containing graft copolymer (a1), the durometer hardness (type A) of the rubber-containing graft copolymer (a1) and the soft elastomer (B), the methyl methacrylate unit content of the rubber-containing graft copolymer (a1) and the (co)polymer (a2) (represented as "MMA content" in Tables 1A and 1B) are measured by the following (1) to (4), respectively.
[0150] (1) Volume average particle size
[0151] The volume average particle size of the rubber polymer (a1-1) in the emulsion was measured at room temperature using "micro track UPA150" (trade name) manufactured by Honeywell Co. The unit is nm.
[0152] It is found that there is substantially no difference between the particle size of the rubber polymer (a1) in the emulsion and the rubber particle size of the rubber polymer (a1) in the resin composition using the rubber polymer (a1), and the former matches the latter.
[0153] (2) Grafting rate
[0154] The graft ratio of the rubber-containing graft copolymer (a1) is calculated by the following formula.
[0155] Grafting rate (mass %) = {[(n) - (m) × L] / [(m) × L]} × 100
[0156] In the above formula, n is the following mass (g): about 1 g [weighing: m (g)] of the rubber-containing graft copolymer (a1) is put into 20 ml of acetone, shaken for 2 hours using an oscillator at a temperature of 25°C, and then centrifuged for 60 minutes using a centrifuge (rotation speed: 23,000 rpm) at a temperature of 5°C to separate the acetone-insoluble component and the acetone-soluble component. The mass (g) of the obtained acetone-insoluble component is n.
[0157] L is the mass (g) of the rubbery polymer (a1-1) contained in the rubber-containing graft copolymer (a1).
[0158] The mass of the rubber polymer (a1-1) can be determined by a method of calculation based on the polymerization formula and the polymerization conversion rate, a method of determination using an infrared absorption spectrum, or the like.
[0159] (3) Durometer hardness (Type A)
[0160] The measurement was carried out according to JIS K6301A type.
[0161] (4) Methyl methacrylate unit content
[0162] Equipment used: Pyrolysis gas chromatograph GC7890 manufactured by Agilent Technologies
[0163] Measurement method: As a pretreatment, acetone solvent was added, and centrifuged twice at 19,000 rpm for 30 minutes, then ethanol solvent was added, extracted at 90°C for 4 hours, and cooled and filtered. The filtered solution was used for gas chromatography analysis.
[0164] The methyl methacrylate unit contents in the acrylic component-containing reinforcement resin (A) and the thermoplastic resin composition were calculated by ratio calculation from the methyl methacrylate unit contents and blending ratios of the components used.
[0165] [Acrylic-containing reinforcing resin (A)]
[0166] As the rubber-containing graft copolymer (a1), the diene rubber-containing graft copolymers (MABS and ABS) and the acrylic rubber-containing graft copolymers (MASA and ASA) obtained in the following Synthesis Examples 1 to 4 were used.
[0167] As the (co)polymer (a2), a styrene-acrylonitrile copolymer (AS) obtained in the following Synthesis Example 5, a styrene-acrylonitrile-methyl methacrylate copolymer (MAS) obtained in the following Synthesis Example 6, and a commercially available product of the following polyacrylic resin (PMMA) were used.
[0168] <Synthesis Example 1: Production of MABS>
[0169] In a glass flask with an internal volume of 10 L and equipped with a stirrer, 45 parts of a polybutadiene emulsion having a volume average particle size of 300 nm (in terms of solid content), 0.3 parts of sodium dodecylbenzenesulfonate and 100 parts of ion exchange water were added, followed by 3 parts of styrene, 2 parts of acrylonitrile and 9 parts of methyl methacrylate. The mixture was heated to 43° C. while being stirred, and then an aqueous solution consisting of 0.02 parts of sodium ethylenediaminetetraacetate, 0.001 parts of ferrous sulfate heptahydrate, 0.08 parts of sodium formaldehyde sulfoxylate dihydrate and 6 parts of ion exchange water and 0.04 parts of cumene hydroperoxide were added, and the reaction was continued for 1 hour.
[0170] Thereafter, a monomer mixture consisting of 9 parts of styrene, 5 parts of acrylonitrile, 27 parts of methyl methacrylate, 1.2 parts of tert-dodecyl mercaptan, and 0.1 parts of isopropylbenzene hydroperoxide, and an aqueous solution consisting of 0.01 parts of sodium ethylenediaminetetraacetate, 0.001 parts of ferrous sulfate heptahydrate, 0.05 parts of sodium formaldehyde sulfoxylate dihydrate, 0.3 parts of sodium dodecylbenzene sulfonate, and 30 parts of ion-exchanged water were added continuously over 4 hours to continue the polymerization reaction.
[0171] After the addition was completed, 0.003 parts of sodium ethylenediaminetetraacetate, 0.0002 parts of ferrous sulfate, 0.01 parts of sodium formaldehyde sulfoxylate dihydrate, 0.02 parts of cumene hydroperoxide and 1 part of ion-exchanged water were further added, and stirring was continued for another hour, followed by cooling to terminate the reaction.
[0172] Then, 0.67 parts of a reaction product of p-cresol-dicyclopentadiene-isobutylene ("SANDWIN-45" manufactured by Toho Chemical) and 0.5 parts of sodium ethylenediaminetetraacetate were added to the reaction product, and coagulated with magnesium sulfate. The reaction product was thoroughly washed with water, dehydrated, and dried at 80°C for 24 hours to obtain a white powdery rubber-containing graft copolymer (MABS).
[0173] The MABS had a polymerization conversion rate of 97.0%, a rubber content of 45%, a grafting rate of 60%, an intrinsic viscosity [η] of 0.24 dl / g (measured at 30° C. in methyl ethyl ketone), and a durometer hardness (type A) of 90 or more.
[0174] The methyl methacrylate unit content of this MABS was 39%.
[0175] <Synthesis Example 2: Production of ABS>
[0176] 120 parts of pure water, 0.5 parts of glucose, 0.5 parts of sodium pyrophosphate, 0.005 parts of ferrous sulfate, and 60 parts of polybutadiene emulsion with a volume average particle size of 280 nm (in terms of solid content) were placed in a reactor purged with nitrogen, and the temperature in the reactor was raised to 65°C while stirring. The polymerization started when the internal temperature reached 65°C, and 30 parts of styrene, 10 parts of acrylonitrile, and 0.02 parts of a chain transfer agent tert-dodecyl mercaptan mixture were continuously added over 5 hours. Simultaneously, an aqueous solution consisting of 0.2 parts of cumene hydroperoxide as a polymerization initiator, 2 parts of potassium oleate, and 20 parts of water was continuously added over 7 hours to complete the reaction. 1 part of 2,2'-methylenebis(4-methyl-6-tert-butylphenol) was added to the obtained emulsion with respect to 100 parts of the solid content of the emulsion, and then the emulsion was coagulated with sulfuric acid, neutralized with sodium hydroxide, washed, filtered, and dried to obtain powdered ABS.
[0177] The rubber content of the ABS was 60%, the graft ratio was 52%, and the durometer hardness (type A) was 90 or more.
[0178] This ABS contains no methyl methacrylate units.
[0179] <Synthesis Example 3: Production of MASA>
[0180] MASA was produced according to the following steps (i) to (ii).
[0181] (i) Production of acrylic rubber polymer emulsion
[0182] Into a 5 L glass reactor equipped with a stirring device, a raw material and auxiliary agent adding device, a thermometer, a heating device, etc., 150 parts of water, 2 parts of sodium dodecylbenzenesulfonate as an emulsifier, 50 parts of n-butyl acrylate (hereinafter abbreviated as BA), and 1 part of allyl methacrylate were charged, and the internal temperature was raised to 60° C. under a nitrogen gas stream while stirring.
[0183] When the temperature reaches 60°C, 0.01 parts of cumene hydroperoxide and an aqueous solution of 0.004 parts of ethylenediaminetetraacetic acid tetrasodium dihydrate, 0.15 parts of sodium formaldehyde sulfoxylate and 0.001 parts of ferrous sulfate dissolved in 10 parts of water are added to the reactor, and polymerization begins at the same temperature.
[0184] One hour after the start of polymerization, the internal temperature of the reactor was maintained at 75°C for 30 minutes to terminate the polymerization reaction and obtain an acrylic rubber polymer emulsion. The polymerization conversion rate at this time was 97%. The volume average particle size of the obtained acrylic rubber was 95 nm.
[0185] (ii) Production of Rubber-Containing Graft Polymers
[0186] 20 parts of methyl methacrylate and 0.2 parts of tert-dodecyl mercaptan were mixed to prepare a monomer mixture (I). 50 parts (in terms of solid content) of the above acrylic rubber polymer emulsion, 10 parts of water, and 0.1 parts of sodium dodecylbenzenesulfonate were added to a 5 L glass reactor equipped with a stirring device, a raw material and auxiliary agent adding device, a thermometer, a heating device, etc., and the temperature was raised to 65°C under a nitrogen flow while stirring. When the temperature reached 65°C, an aqueous solution of 0.004 parts of ethylenediaminetetraacetic acid tetrasodium dihydrate, 0.15 parts of sodium formaldehyde sulfoxylate, and 0.001 parts of ferrous sulfate dissolved in 20 parts of water and an aqueous solution of 0.4 parts of tert-butyl hydroperoxide dissolved in 40 parts of water were added continuously over 3 hours to start polymerization. The temperature was raised to 70°C from the start of polymerization and then maintained at 70°C. After the continuous addition was completed, the polymerization was terminated by maintaining the same temperature for 60 minutes. The copolymer latex was coagulated, washed with water, and dried to obtain powdered MASA.
[0187] The rubber content of the MASA was 50%, the graft ratio was 70%, and the durometer hardness (type A) was 90 or more.
[0188] The methyl methacrylate unit content of this MASA was 19%.
[0189] <Synthesis Example 4: Production of ASA>
[0190] ASA was obtained in the same manner as in the preparation of MASA in Synthesis Example 3 except that a monomer mixture (II) prepared by mixing 38 parts of styrene, 12 parts of acrylonitrile and 0.2 parts of tert-dodecyl mercaptan was used instead of the monomer mixture (I).
[0191] The rubber content of the ASA was 51%, the graft ratio was 85%, and the durometer hardness (type A) was 90 or more.
[0192] This ASA contains no methyl methacrylate units.
[0193] <Synthesis Example 5: Production of AS>
[0194] A monomer mixture consisting of 120 parts of water, 0.002 parts of sodium alkylbenzene sulfonate, 0.5 parts of polyvinyl alcohol, 0.3 parts of azoisobutyronitrile, 0.5 parts of tert-dodecyl mercaptan, 26 parts of acrylonitrile and 74 parts of styrene was used in a nitrogen-purged reactor, and a portion of styrene was gradually added while heating from an initial temperature of 60° C. for 5 hours to 120° C. Further, after reacting at 120° C. for 4 hours, a polymer was taken out to obtain an acrylonitrile-styrene copolymer (AS) having acrylonitrile / styrene = 26 / 74 (mass ratio).
[0195] The mass average molecular weight (Mw) and molecular weight distribution (Mw / Mn) of the obtained AS were measured by polystyrene conversion using GPC (GPC: "GPC / V2000" manufactured by Waters, column: "Shodex AT-G+AT-806MS" manufactured by Showa Denko K.K.) with o-dichlorobenzene (145° C.) as the solvent. The mass average molecular weight (Mw) was 110,000, and the molecular weight distribution (Mw / Mn) was 2.3.
[0196] AS does not contain methyl methacrylate units.
[0197] <Synthesis Example 6: Production of MAS>
[0198] A monomer mixture was prepared by mixing 21 parts of styrene, 7 parts of acrylonitrile, 72 parts of methyl methacrylate, 0.3 parts of tert-dodecyl mercaptan and 0.2 parts of diisopropylbenzene hydroperoxide.
[0199] Into a 10L glass reactor equipped with a stirring device, a raw material and auxiliary agent adding device, a thermometer, a heating device, etc., 150 parts of water and 2 parts of sodium dodecylbenzenesulfonate as an emulsifier were added, and the internal temperature was raised to 55°C under a nitrogen stream while stirring. When the temperature reached 55°C, the above-mentioned monomer mixture and an aqueous solution in which 0.09 parts of ethylenediaminetetraacetic acid tetrasodium dihydrate, 0.003 parts of ferrous sulfate heptahydrate and 0.2 parts of sodium formaldehyde sulfoxylate were dissolved in 24 parts of water were continuously added over 5 hours.
[0200] From the start of the addition of the monomer mixture to 1 hour later, the internal temperature was raised to 67° C. and then maintained at 67° C. After the continuous addition was completed, 0.05 parts of diisopropylbenzene hydroperoxide was added, and the internal temperature was further maintained for 1 hour to terminate the polymerization reaction. The copolymer emulsion was coagulated with calcium chloride, washed with water, and dried to obtain a powdery copolymer (MAS).
[0201] The polymerization conversion rate at this time was 98%, and the intrinsic viscosity [η] was 0.33 dl / g (measured at 30°C in methyl ethyl ketone).
[0202] The methyl methacrylate unit content of this MAS was 71%.
[0203] <pmma>
[0204] As the polyacrylic acid-based resin, PMMA "ACRYPET (registered trademark) VH5" (methyl methacrylate unit content: 99.5%) manufactured by Mitsubishi Chemical Corporation was used.
[0205] [Soft elastomer (B)]
[0206] As the soft elastomer (B), the following commercially available products were used.
[0207] Styrene-based elastomer: Hydrogenated block copolymer SEBS "Dynaron (registered trademark) DR8903P" manufactured by JSR Corporation (durometer hardness (type A): 49)
[0208] Acrylic elastomer: soft acrylic resin "Parapet (registered trademark) SA-FW001" manufactured by KURARAY Co., Ltd. (durometer hardness (type A): 70, methyl methacrylate unit content: 34%)
[0209] [Examples 1 to 9 and Comparative Examples 1 to 4]
[0210] <Preparation and Evaluation of Thermoplastic Resin Composition for Physical Property Measurement>
[0211] The components shown in the following Tables 1A and 1B were mixed in the mixing ratios shown in Tables 1A and 1B. Then, 0.2 parts of "ADK STAB (registered trademark) A-60" (tetrakis[methylene-3-(3',5'-di-tert-butyl-4'-hydroxyphenyl)propionate]methane) manufactured by ADEKA Corporation was mixed, and melt-kneaded at a barrel temperature of 220°C using a twin-screw extruder (model name "TEX44", "The Japan Steel Works") to form pellets. The pellets of the obtained thermoplastic resin composition were used to prepare the following molded products (1) to (4), which were respectively subjected to the following measurements and evaluations. The evaluation results are shown in Tables 1A and 1B.
[0212] <Production of Molded Product (1)>
[0213] Using an injection molding machine "IS100GN" (trade name) manufactured by Toshiba Machine Co., Ltd., a test piece of 120 mm × 80 mm × 2 mm was produced under the conditions of a resin temperature of 220°C, a mold temperature of 50°C, an injection speed of 40 mm / s, and an injection pressure of 100 MPa. As a molding mold, a mold for leather grain (texture No.; TH-894) having concavoconvexity on the inner surface (the depth of the concave portion is 100 μm) was used.
[0214] <Production of Molded Products (2)>
[0215] Using an injection molding machine "J110AD-180H" (model name) manufactured by Japan Steel Works, Ltd. with a barrel set temperature of 220 °C and a mold temperature of 50 °C, a dumbbell-shaped test piece (without weld) having a gate on one side was produced. Next, the central portion of the dumbbell-shaped test piece was cut out to produce a test piece without weld (dimensions: 80 × 10 × 4 mm).
[0216] <Manufacture of molded product (3)>
[0217] Using a mold having gates at both ends and forming a weld in the center of the test piece, a dumbbell-shaped test piece having a weld was produced using an injection molding machine "J110AD-180H" (model name) manufactured by Japan Steel Works, Ltd. with a barrel set temperature of 220 °C and a mold temperature of 50 °C. Next, the central portion of the dumbbell-shaped test piece having a weld was cut out to produce a test piece having a weld in the central portion (dimensions: 80 × 10 × 4 mm).
[0218] <Manufacture of molded product (4)>
[0219] Using an injection molding machine "J110AD-180H" (model name) manufactured by Japan Steel Works, Ltd. with a barrel set temperature of 220 °C and a mold temperature of 50 °C, a test piece (dimensions: 80 × 10 × 4 mm) having a gate on one side was produced.
[0220] <Measurement of MIU value (KES hand feeling measurement)>
[0221] Using a "Friction Sensation Tester KES-SE" (product name) manufactured by Katotech, the MIU value of the textured surface of the molded product (1) was measured. The MIU value (average coefficient of friction) is an index of non-slip property, and the higher the value, the less likely it is to slide.
[0222] <Measurement of durometer hardness (Type D)>
[0223] Using the molded product (1), the measurement was carried out in accordance with JIS K7215.
[0224] <Measurement of flexural modulus of elasticity>
[0225] Using the molded product (2), the measurement was carried out at 23 °C in accordance with ISO178. The unit is "MPa".
[0226] <Measurement of total light transmittance>
[0227] Using the molded product (1), the measurement was carried out in accordance with JIS K7361.
[0228] <Measurement of haze (RH plate)>
[0229] The molded article (1) was measured for haze using a haze meter (manufactured by Murakami Color Laboratory Co., Ltd.) The lower the haze, the higher the transparency.
[0230] <Production and Evaluation of Thermoplastic Resin Composition for Laser Marking>
[0231] The components shown in Tables 1A and 1B below were supplied to a Henschel mixer in the ratios shown in Tables 1A and 1B, and then, as antioxidants, 0.2 parts of "ADK STAB (registered trademark) 2112" (tris(2,4-di-tert-butylphenyl)phosphite) manufactured by ADEKA, 0.2 parts of "IRGANOX (registered trademark) 1010" (tetrakis[methylene 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]methane) manufactured by Ciba Specialty Chemicals, and 0.05 parts of carbon black having a particle size of 50 nm (trade name "RCF#20", manufactured by Mitsubishi Chemical Corporation) were added to 100 parts of the total, and mixed at 25° C. Then, the mixture was supplied to a twin-screw extruder (model name "BT40", manufactured by Research Laboratory of Plastics Technology Co., Ltd.) for melt kneading to obtain pellets of a thermoplastic resin composition for laser marking.
[0232] In addition, the cylinder setting temperature during melt kneading was set to 180°C to 220°C.
[0233] <Evaluation of Laser Marking Properties>
[0234] The obtained pellets were introduced into an injection molding machine (model name "EC60", manufactured by Toshiba Machine Co., Ltd.) or an injection molding machine (model name "J35AD", manufactured by Nippon Steel Works), and molded into plate-shaped test pieces (80 mm×55 mm×2.4 mm) at a cylinder setting temperature of 180°C to 240°C.
[0235] The surface of the plate-like test piece was irradiated with laser light using a diode-excited laser marker (model name "RSM30D", manufactured by Rofin-Baasel) at a scanning speed (printing speed) of 400 mm / s, a wavelength of 1,064 nm, a frequency of 5,500 Hz, a current of 28 A, and a power of 30 W to mark white characters from the resin.
[0236] The color rendering properties (clarity and visibility) of the irradiated portion were evaluated according to the following criteria. The results are shown in Tables 1A and 1B.
[0237] "◎": Very good (clarity and visibility are both very good)
[0238] "○": Good (clearness and visibility are good, no practical problems)
[0239] "△": Good (either clarity or visibility is poor)
[0240] "×": Poor (both clarity and visibility are poor)
[0241] [Table 1A]
[0242]
[0243] [Table 1B]
[0244]
[0245] The following can be seen from Tables 1A and 1B above.
[0246] Examples 1 to 9 using the thermoplastic resin composition of the present invention not only have excellent laser markability, but also have excellent softness, tactile feel (gripping feel), sliding difficulty (MIU value), and further optical properties. In contrast, Comparative Examples 1 to 4 that do not satisfy the condition of formula (1) have the result that both laser markability and tactile feel cannot be achieved.
[0247] Although the present invention has been described in detail using specific embodiments, it will be apparent to one skilled in the art that various modifications can be made without departing from the spirit and scope of the present invention.
[0248] This application is based on Japanese patent application No. 2022-126425 filed on August 8, 2022, and its entire contents are cited by reference.
[0249] Industrial Applicability
[0250] The molded article of the present invention using the thermoplastic resin composition of the present invention has excellent laser marking properties, and the surface is not easy to slide, and the tactile feeling such as grip is good. Therefore, it can be appropriately used as an item that needs to be operated by hand or is not easy to slip from the hand, and a product that is not easy to slide and has good grip performance can be provided. In addition, it is not limited to the grip of the hand, and can also be used as a component of the grounding surface of a personal computer or a printer to show an anti-slip effect. Therefore, the usefulness of the molded article of the present invention is extremely high.< / pmma>
Claims
1. A thermoplastic resin composition comprising the following components (A) and (B), wherein when the content of methyl methacrylate units in the total of 100% by mass of the components (A) and (B) is X% by mass and the content of the component (B) is Y% by mass, the following formula (1) is satisfied: 0.1 <Y / (X+Y)<0.9…(1) Component (A): a reinforcing resin containing an acrylic component, which is composed of a rubber-containing graft copolymer (a1) having a durometer hardness (type A) of 90 or more, or the rubber-containing graft copolymer (a1) and a (co)polymer (a2) not containing a rubber polymer, wherein the rubber-containing graft copolymer (a1) and / or the (co)polymer (a2) contain methyl methacrylate units; Component (B): A soft elastomer having a durometer hardness (type A) of less than 90.
2. The thermoplastic resin composition according to claim 1, wherein The content Y of the component (B) in 100% by mass of the total of the component (A) and the component (B) exceeds 20.0% by mass.
3. The thermoplastic resin composition according to claim 1 or 2, wherein The rubber-containing graft copolymer (a1) is one or more selected from the group consisting of methyl methacrylate-acrylonitrile-butadiene-styrene graft copolymers, acrylonitrile-styrene-acrylic rubber graft copolymers, methyl methacrylate-acrylonitrile-styrene-acrylic rubber graft copolymers and acrylonitrile-butadiene-styrene graft copolymers.
4. The thermoplastic resin composition according to claim 1 or 2, which is a thermoplastic resin composition for laser marking.
5. A molded article obtained by molding the thermoplastic resin composition according to claim 1 or 2.
6. An article, wherein the surface of the molded article according to claim 5 is laser marked.
Citation Information
Patent Citations
JP1988004841B2
Hydrogenation of living polymer
JP1988005401B2
Production of rubber modified thermoplastic resin
JP1989297413A
Hydrogenated block copolymer and composition thereof
JP1990133406A
Butadiene rubber reinforced resin and its composition
JP2002003548A